Hubungan dan Integrasi Mahasiswa Minoritas dengan Mahasiswa Mayoritas Muslim di UIN K.H. Abdurrahman Wahid Pekalongan - Merlina Gustin; Novita Safitri; Rafiffi Ali Hanan Santosa; Ahmad Tubagus Surur (JOURNAL SAINS STUDENT RESEARCH, 2025)
The purpose of this research is to find out how the form and inhibiting factors of social interaction between minority students and Muslim majority students. The method used in this research is descriptive qualitative method. The results showed that minority students and Muslim majority students established a good relationship. They highly prioritize attitudes and a high sense of tolerance by accepting and appreciating existing differences. (1) the form of interaction that occurs between the two is the attitude of not discriminating and still appreciating the differences of minority students. (2) There are inhibiting factors in the interaction between Christian and Islamic students. Internal factors are introverted, closed, shyness and lack of confidence. The relationship formed from minority students and lecturers is quite good, the lecturer really appreciates minority students by differentiating learning methods according to the ability of minority students.